2014
DOI: 10.1007/s13197-014-1501-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified atmospheric packaging on the shelf life of Kalakand and its influence on microbial, textural, sensory and physico-chemical properties

Abstract: Kalakand, a popular traditional milk sweet of Indian sub-continent, was packaged under air and modified atmospheric packaging (MAP) conditions (98 % N 2 , 98 % CO 2 and 50 % N 2 : 50 % CO 2 ). The samples were stored at 10, 25 and 37°C and evaluated for various physico-chemical, microbial, textural and sensory changes, in order to establish the applicability of MAP for storage of Kalakand. It could be established that the MAP conditions of 50 % N 2 : 50 % CO 2 and storage at 10°C, were the most suitable condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 17 publications
14
15
0
Order By: Relevance
“…This may be due to higher khoa content of Kalakand and lower moisture content of sample. These findings are in agreement with Jain et al, (2015) observed variation in textural properties of Kalakand. Hardness of the product is directly related to moisture content, the hardness of Kalakand ranged between 474.57 ± 0.24 ba to 1725.35 ± 0.69 ca (Fig.…”
Section: Hardnesssupporting
confidence: 92%
See 1 more Smart Citation
“…This may be due to higher khoa content of Kalakand and lower moisture content of sample. These findings are in agreement with Jain et al, (2015) observed variation in textural properties of Kalakand. Hardness of the product is directly related to moisture content, the hardness of Kalakand ranged between 474.57 ± 0.24 ba to 1725.35 ± 0.69 ca (Fig.…”
Section: Hardnesssupporting
confidence: 92%
“…The variation could be due to the difference in raw material used, processing parameter used during manufacturing and chemical composition of Kalakand. This is supported by Jain et al, (2015) reported that the adhesiveness of Kalakand ranged between 0.26 ± 0.02 ab to 0.47 ± 0.03 aa g.s.…”
Section: Adhesivenesssupporting
confidence: 73%
“…One of the reasons for the short shelf life is the products' high moisture content viz. about 40-50 g/100 g product (Jain et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Coliforms in the samples were estimated by plating appropriate dilutions (10− 2) on Violet Red Bile Agar (VRBA) before being incubated at 37 °C for 24 h (Jain et al, 2015 andAbdalla andAhmed, 2010).…”
Section: Microbial Analysismentioning
confidence: 99%